Processo de eletroencapsulação para a obtenção de microcápsulas contendo Spirulina platensis - Santos, Maristela Raupp dos (2022)
Spirulina platensis (Sp) biomass has motivated researches for its incorporation into foods due to its nutraceutical potential, however, being present in a food matrix, it can give undesirable flavor and odor, in addition to losing part of its bioactivity and presenting an inhomogeneous aspect. Microencapsulation is one of the technologies that can minimize these effects. The objective was to evaluate the electroencapsulation method for the microencapsulation of the whole biomass of Sp. Tests were carried out with different wall materials: pectin (BTM) and Whey Protein Concentrate (WPC) and later without pectin and including glycerol in the composition of the suspensions; flow (0.15, 0.30, 0.49 and 1.2 mL/h), collector distance (8 and 12 cm), capillary diameter (0.3 and 0.7 mm) and voltage (16, 17, 18, 20, 22, 25 and 28 kV) parameters were also studied in own manufacturing electroencapsulation equipment. The suspensions containing 4 and 10 g/100 mL of pectin obstructed the capillaries and the increase in flow and voltage did not help in unblocking and consequently in the formation of microcapsules (MC). At the concentration of 2 g/100 mL of pectin, material was lost by dripping. In the suspensions containing glycerol, a fine powder was formed that was characterized by optical and scanning microscopy (SEM) and the interactions analyzed by Fourier transform infrared spectroscopy (FTIR), from which it was possible to observe the formation of regular shaped spherical MC . Based on the observed yield results, the parameters flow (0.15 mL/h), collector distance (8 cm), voltage (28 kV) and capillary diameter (0.7 mm) were fixed. Subsequently, the concentrations of CPSL (35 and 50 g/100 mL of suspension) and glycerol (5.75; 6.5 and 11 g/100 mL of suspension) were varied and the concentration of Sp (0. 05 g/100 mL of suspension) was fixed to evaluate the effects on yield, moisture and water activity (Aw), solubility and hygroscopicity responses. The assay containing 50 g/100 mL of CPSL and 6.5 g/100 mL of glycerol resulted in higher yield (68.3%), lower moisture content (16.7%) and lower percentage of hygroscopicity (16.2 %) compared to the other tests. Regarding Aw and solubility, the assays did not differ from each other. The morphological characterization showed spherical MC, smooth with slight roughness and sizes between 1 to 3 μm can be inferred. The thermogravimetric analysis showed the degradation of glycerol at 150 °C and the degradation of other materials from 200 °C. The results demonstrated the feasibility of the electroencapsulation technique for the development of MC containing Sp using CPSL and glycerol as wall materials avoiding the use of organic solvents and/or high temperatures.